The Many Faces of Persistent Stapedial Artery: CT Findings and Embryologic Explanations - LoVerde, Z.J. (AJNR Am J Neuroradiol, 2021)
Persistent stapedial artery is a vascular anomaly with both clinical and surgical implications. Because of its scarcity, however, it remains underrecognized on imaging. Presented here is a series of 10 cases, demonstrating characteristic CT findings associated with this vascular anomaly and its most common pathognomonic imaging signs. The variable morphologic configurations and their corresponding embryologic underpinnings are described. Clinical and surgical implications of this rare anomaly are discussed.